(untitled) - Lilja, David J. (Cambridge, 2005)
Using Verilog, a leading commercial hardware description language, this text describes how to specify, design, and test a complete digital system. After a brief introduction to the Verilog language, the instruction set architecture (ISA) for the simple VeSPA (Very Small Processor Architecture) processor is defined. The remainder of the book demonstrates how both behavioral and structural models can be developed and intermingled in Verilog.
Keywords: Verilog (Computer hardware description language),Electronic digital computers,Verilog (ngôn ngữ mô tả phần cứng máy tính),Kỹ thuật số máy tính điện tử; Design and construction,Thiết kế và xây dựng